2016
DOI: 10.1177/000313481608200318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the General Surgery Intern Boot Camp

Abstract: The aim of our study is to evaluate the effectiveness of newly implemented general surgery intern boot camp. A 2-day didactic and skills-based intern boot camp was implemented before the start of clinical duties. Participants who did not attend all boot camp activities and had prior postgraduate training were excluded. A survey utilizing a 5-point Likert scale scoring system was used to assess the participants’ confidence to perform intern-level tasks before and after the boot camp. Subgroup analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…This supports previous work described in the veterinary field (8), but also supports data from other fields. Educational boot camps are widely used in many fields and are gaining popularity, including advanced human medical training (24,25), the basic sciences (26), and undergraduate education (27), though their influence on advanced medical skills has been questioned (28). However, to our knowledge, none of these boot camps have correlated student performance in subsequent programs (28).…”
Section: An Anatomy Precourse Predicts Students' Performance Within Tmentioning
confidence: 99%
“…This supports previous work described in the veterinary field (8), but also supports data from other fields. Educational boot camps are widely used in many fields and are gaining popularity, including advanced human medical training (24,25), the basic sciences (26), and undergraduate education (27), though their influence on advanced medical skills has been questioned (28). However, to our knowledge, none of these boot camps have correlated student performance in subsequent programs (28).…”
Section: An Anatomy Precourse Predicts Students' Performance Within Tmentioning
confidence: 99%
“…Pre-internship programmes are usually of limited duration (several hours to several weeks) and focus on the acquisition of discrete skills. Self-assessment is usually used in evaluation of these programmes [ 36 , 40 , 41 ], although some have implemented objective knowledge assessments [ 42 ]. While participants often demonstrate improved self-confidence [ 36 ], which has proven to be durable in some settings [ 40 ], other authors have not reported on the phenomenon of tempered self-confidence that we observed in a subset of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Kenny and colleagues 1 provide a good first step in the systematic evaluation of simulation and live operating boot camp experiences. 1 Others have demonstrated similar results in improving the confidence of trainees, 2,3 and it is well known that confidence is a key trait of a successful surgeon. Long-term sustainability and applicability of knowledge gained in boot camps (as a significant improvement relative to others who have trained in the traditional manner) were not clearly demonstrated.…”
mentioning
confidence: 91%